Exploring STEM Attitudes among First-year Early Childhood and Primary Preservice Teachers: Gender and Regional Insights in Western Australia - Sims, Craig; Walker, Rebecca; Treagust, David (Infonomics Society, 2024)
Understanding how future educators approach STEM is crucial for developing effective teacher education programs. This study examined STEM attitudes among 146 first-year preservice teachers in Western Australia, comparing early childhood and primary education cohorts while considering gender and geographical location. Using an adapted T-STEM survey), results revealed that primary preservice teachers demonstrated higher efficacy in science and technology (p < 0.01), while their early childhood counterparts showed stronger attitudes toward STEM leadership (p < 0.032). Male participants reported higher mathematics efficacy (p < 0.001) and technology confidence (p < 0.001), though female participants expressed notably positive attitudes toward leadership roles. Preservice teachers residing in regional areas demonstrated more optimistic views toward STEM instruction (p <0.007) compared to their urban peers. These findings suggest the need for differentiated approaches in teacher education programs, including targeted support for technical skills in early childhood education, gender-responsive strategies, and specialised resources for both urban and regional contexts.